IMPLEMENTASI PERATURAN BUPATI SRAGEN NOMOR 49 TAHUN 2017 TENTANG PETUNJUK PELAKSANAAN PERATURAN DAERAH KABUPATEN SRAGEN NOMOR 6 TAHUN 2016 TENTANG PENANGGULANGAN HIV/AIDS TAHUN 2019 - Sutrisno, Sutrisno; Qomarudin, Qomarudin; Winarti, Liliek (JI@P, 2020)
Increased findings of the new case of HIV/AIDS, the presence of Stigma anddiscrimination against ODHA that underlies the policy of Regent Regulation No.49 year 2017 about implementation Directive District Regulation Sragen No. 6year 2016 on HIV/AIDS prevention. And until now, still have problems with theimplementation of HIV/AIDS prevention in Sragen district. To analyze theimplementation of regulation of Regent Sragen Number 49 year 2017 aboutimplementation Directive District Regulation Sragen Number 6 year 2016 aboutthe prevention of HIV/AIDS in Sragen District.Types of descriptive research with a qualitative approach. Sampling techniquesby purposive sampling, research samples as many as 4 people from the organizersof policy providers, among others: Dinkes District Sragen, KPA District Sragen,NGO Muslimat NU and KDS Sukowati District Sragen. Data analysis techniquesused are data collection, data reduction, data presentation and withdrawal ofconclusions.Implementation of HIV/AIDS prevention policy in Sragen district has not beencarried out with maximum. This is because there are some obstacles, amongothers: Information distribution is less than the maximum because the coveragearea is too wide and long distance to the hinterland, resources are still lacking,lack of the commitment of the officers trained on the construction of the bodyODHAdi. Advice: continuous transmission of information through innovativeoutreach and programs, eliminating negative stigma and discrimination onODHA, strengthening coordination to keep the program running better andsmoother.